Lapatinib-induced enhancement of mitochondrial respiration in HER2-positive SK-BR-3 cells: mechanism revealed by analysis of proteomic but not transcriptomic data - Kamashev, Dmitry; Shaban, Nina; Zakharova, Galina; Modestov, Alexander; Kamynina, Мargarita; Baranov, Sergey; Buzdin, Anton (Frontiers in Molecular Biosciences, 2024)
Dual inhibitors of HER2 and EGFR, such as lapatinib, have shown significant efficacy for the therapy of HER2-positive breast cancer. Previous experiments showed that in cell cultures, the efficacy of lapatinib was significantly reduced by exposure to human serum and human epidermal growth factor (EGF). At the proteomic and transcriptomic levels, we examined the changes in the HER2-positive breast cancer cell line SK-BR-3 profiles upon treatment with lapatinib, either alone or in combination with human serum or EGF. Proteomic profiling revealed 350 differentially expressed proteins (DEPs) in response to lapatinib treatment at concentrations that induced cell growth arrest. Addition of human serum or EGF in combination with lapatinib prevented cell growth inhibition, and this combination treatment returned the expression of ~93% of DEPs to drug-free levels for both human serum and EGF. Gene ontology enrichment and OncoboxPD pathway activation level analysis showed that lapatinib addition influenced mostly common functional processes revealed in RNA-and protein-based assays. However, a specific feature was observed at the proteome level: addition of lapatinib increased the expression of proteins associated with mitochondrial function and cellular respiration. This feature was not observed when using RNA sequencing data for the same experiments. However, it is consistent with the results of the resazurin test, which showed a 1.8-fold increase in SK-BR-3 cellular respiration upon exposure to lapatinib. Thus, we conclude that enhanced cellular respiration is a novel additional mechanism of action of lapatinib on HER2positive cancer cells.